Perturbations in upper tropospheric easterlies and Bay cyclones - GUPTA, G. R.; CHAND, RAMESH (MAUSAM, 1994)
Pertu rbat ions in th e form of large amplitude troughs or dosed circu lation s are absen ted to develop in the weak upper tro posph eric easterlies at 200 and 100 hPs levels over no rthwest Pacific am! adjoining Indi an Ocean. Occasionally, these are 2 to 3-C colder than their immediate enviro nme nt. These systems are observed 10 propagate downwards durina their westwa rd tr aversal : while ove r 500 h Ps th ese in teract with and activate the lower troposph eric cyclonic circ ula tion to intensify into a depression/cyclonic stem}. At this stage, the cyclonic:ci rcu l" tion in upper tropo sph eric levels is observed 10 vanish: this may, however. re-appear subseq uently on fUl1ho r int ensification of the cyclonic sto rm . Evidence of such interaction a nd intensification is adduced with a few t)'pica) synoptic systems .